Evaluating the effect of tonsillectomy on anti-streptolysin O titre levels in the pediatric population. - Iftikhar, Umera; Najeeb, Sara; Ali, Muhammad; Malik, Farhat Jabeen (Journal of Rawalpindi Medical College, 2025)
Objective: To evaluate the effect of tonsillectomy on anti-streptolysin O (ASO) titre levels in children. Methodology: 48 patients 5 -15 years of age with ASO titre > 200IU/ml undergoing elective tonsillectomy were included in the study.ASO titre was measured at 1 month, 2 months and 3 months after tonsillectomy. Data analysis was done at SPSS 21. P-value of < 0.05 was taken as significant. Results: After tonsillectomy reduction of ASO titre to less than 200IU/ml occurred in 3 (6%), 27 (56%) and 46 (96%) patients at 1st, 2nd and 3rd monthly follow up respectively. Conclusion: Tonsillectomy significantly reduces ASO titre levels in pediatric patients with recurrent tonsillitis. This reduction suggests that tonsillectomy can effectively mitigate the immune response to streptococcal infections.